Carnell, Rab. Interview about his work as a CBC radio broadcaster. - Swain, Hector K. (1990)
Rab Carnell talks about his work with the CBC as a radio broadcaster, primarily with the Farm and Fisheries Broadcasts. Carnell also talks about other radio programs at the time, and the 4-H clubs. 00:00 - Hector Swain introduces the interview; 01:45 - Rob Carnell talks about Newfoundland joining confederation and the CBC taking over the radio broadcasting; Farm and Fish broadcasts; communication in Newfoundland and Labrador; 07:25 - Fishermen's reaction to government programs; 09:16 - Where the fishermen caught fish; 10:38 - Talks about depending on the fishermen when doing the program; How they got information; 14:00 - Carnell talks about the significance of early radio and what areas could get CBC radio at the time; 16:00 - Swain talks about radio and communication in small communities; Communication between communities; 18:40 - The programs on CBC Radio and what he was involved in; 21:45 - Morning Devotion program; The Gerald S. Doyle bulletin; 25:40 - Carnell and Swain talk about Aubrey "Mac" MacDonald; 27:50 - Bob MacLeod 29:30 - This is Britain Calling with Margot Davis; 30:33 - Carnell talks about the end of the Farm Broadcast; what people were interested in; 35:40 - Carnell talks about 4-H clubs; 38:10 - various topics and skills they would discuss on the radio; 40:07 - Civic responsibility, tells story about being discouraged after visiting a house; 41:58 - Talks about communication in the province and the telegraph system; 44:40 - Talks about Rural Reconstruction.